First measurement of neutrons produced by deuterium fusion reactions in SPIDER. (1st February 2022) - McCormack, O.; Giacomelli, L.; Croci, G.; Muraro, A.; Mario, I.; Zuin, M.; Cordaro, L.; Gorini, G.; Cippo, E.P.; Grosso, G.; Rigamonti, D.; Rebai, M.; et al.
Abstract: The inaugural deuterium acceleration campaign in the SPIDER negative ion source facility in Padua has recently taken place. The first neutrons generated by deuterium-deuterium beam-target fusion reactions (2.45 MeV) have been recorded, occurring from the collision of accelerated deuterium with deuterium absorbed by the calorimeter of SPIDER. A neutron detector based on a novel EJ276 plastic scintillator has been employed to successfully measure the neutron flux, which shows strong agreement with the extracted current of the acceleration grid. We have performed neutron-gamma pulse shape discrimination with the EJ276 device at SPIDER combined with direct spectroscopic comparisons of the D-D neutrons with data from the Frascati neutron generator ( 241 AmB quasi-monoenergetic 2.5 MeV). Despite the low statistics produced in this first campaign, both pulse shape discrimination and spectral analysis of the fusion neutrons was viable. The success of these first measurements has led to the installation of an array of 6 new scintillators to be used for further physical studies in future campaigns.